The risk factors and impact of subchorionic hematoma in the first trimester in IVF twin pregnancies: a prospective cohort study - Mei, Youwen; Lin, Yonghong; Guo, Xiaoli; Zhang, Yangping; Wang, Fang (Frontiers in Medicine, 2023)
Objective This study aimed to identify the risk factors for subchorionic hematoma (SCH) in the first trimester of in vitro fertilization (IVF) twin pregnancies and investigate the impact of SCH on pregnancy outcomes. Study design A prospective cohort study was conducted at Chengdu Women and Children's Central Hospital. The study recruited patients who were identified with twin pregnancies in the first trimester, undergoing IVF treatment from January 2020 to May 2021. The demographic characteristics and pregnancy outcomes were compared between the SCH and the non-SCH groups. A logistic regression analysis was used to determine the risk factors for SCH and adverse pregnancy outcomes. Results In the first trimester, 38% of patients developed SCH. The independent risk factors for SCH included male factor, hydrosalpinx, polycystic ovary syndrome (PCOS), previous miscarriage, and adenomyosis. With respect to the pregnancy outcomes, only the rate of twin pregnancy loss before 20 gestational weeks was significantly higher in the SCH group than in the non-SCH group. After adjusting for the confounding factors, the presence of SCH diminished the ovarian reserve, and previous miscarriage was independently related to twin pregnancy loss before 20 gestational weeks. Conclusion This may be the first study to evaluate the risk factors of SCH in twin pregnancies who underwent IVF-ET/FET treatment, which may provide some theoretical basis for clinical practice in the future. Furthermore, it was found that the occurrence of SCH was associated with the loss of both pregnancies before 20 gestational weeks. Therefore, these patients should be offered increased surveillance and timely treatment.